"Bid the players make haste": Speed-Making and Motion Sickness in Hamlet. - NORTHWAY, KARA (Shakespeare Studies (Rosemont Publishing & Printing Corporation), 2016)
The article presents the criticism of William Shakespearean, poet play "Hamlet,". It mentions that the scenes in the play mismatch speedy discourse heard and action that disorient the senses of the characters. It states that the play uses characters and audience disorientation in the concert. It focuses on the cultural validation of decorum in speed.